(untitled) (Comprehensive Journal of Science, 2025)
Libya entered the field of chemical industries in 1980, and the quality of its products reached an excellent level that earned the appreciation of many countries. Libya also received top awards in the field of quality from several international organizations. The production of factories was studied over the period from 1984 to 2003, with time represented by machine operating hours and downtime, for the purpose of analysis and study. Some statistical methods, including regression, were applied to select the appropriate regression model to represent the expected relationship between production and machine working and idle hours.